A decade of systematic literature review on student experience in mobile learning - Radzali, Haslinda; Luqman, Azyanee; Ismail, Mohd Nasir (International Journal of Accounting, Finance and Business, 2025)
Student experience encompasses pragmatic quality (usability and functionality) and hedonic quality (satisfaction and enjoyment) while using mobile devices for educational purposes. However, the student experience in mobile learning depends on technology and human quality. Therefore, this article focuses on a systematic literature review of factors contributing to student experience in mobile learning. For this study, articles were selected from two significant databases, Scopus and Web of Science, and a supporting database, Google Scholar, from 2015 until 2024. Consequently, 15 related studies were found concerning factors of student experience in mobile learning. Three major themes emerged from the thematic analysis of this review: technology and application quality, emotion quality and student experience quality. The results elaborate on the factors that can contribute to student experience. Factors influencing student experience in mobile learning should be explored in future research to support Sustainable Development Goal 4, which ensures quality education for all.